Digitalisasi Holistik Ekonomi Kreatif Batik Tulis Tanjung Bumi dan Tujuan Pembangunan Berkelanjutan - Zaeni Miftah; Indah Purnama Sari (Haka Vyza Media, 2026)
This exploratory qualitative study investigates the opportunities and obstacles within Tanjung Bumi’s hand-drawn batik industry to formulate effective long-term digital growth strategies. Utilizing a multi-method approach including observations, interviews, focus groups, and literature reviews the research employs thematic analysis to process and interpret the data. To ensure findings are robust and valid, data triangulation was applied. The results indicate that successful digitalization requires more than just a shift in marketing; it demands the creation of a comprehensive digital ecosystem. By integrating cultural conservation with community involvement, this model aligns with sustainable development goals, fostering an equitable and resilient economy.